Smart and Sustenaible Cities: A Perspective for the cityof Sorriso in Mato Grosso State - Ravache , Rosana Lia; Enoré, Priscilla Tábida Silva; Snizek Junior , Pedro Nessi; Palmisano , Angelo (National Journal of City Management, 2024)
With the growth of the urban population, parallel to the increase in the urbanization of urban centers, challenges arise for which intelligent and sustainable solutions need to be found. It is by using technology as an ally in caring for the environment that conscious urban development will be achieved. Unfortunately, the model imposed on cities does not prioritize issues essential to human development, such as urban infrastructure focused on people and the environment. The justification for this research lies in new technologies, strong allies of equations aimed at urban development and infrastructure issues aimed at the social and environmental comfort of cities, aiming to analyze, within the context of the city of Sorriso, the paths to a city smart and sustainable, with a focus on urban mobility, given the high number of traffic accidents occurring in the urban core. To meet this end, the research methodology used field data collection, documentary and bibliographic material based on authors who address the theme of smart and sustainable cities and could be related to the city of Sorriso, which aims to become a smart and sustainable city.